Techno-economic analysis of a hydraulic transmission for floating offshore wind turbines. (June 2020) - Roggenburg, Michael; Esquivel-Puentes, Helber A.; Vacca, Andrea; Bocanegra Evans, Humberto; Garcia-Bravo, Jose M.; Warsinger, David M.; Ivantysynova, Monika; Castillo, Luciano
Abstract: Mechanical gearboxes have one of the highest failure rates of wind turbine components while being one of the most expensive parts to replace or service. They are easily fatigued and have a low power rating relative to their size and mass. In this article, hydraulic transmissions are proposed as an alternative to mechanical drive trains and their feasibility has been established, particularly for offshore wind turbine applications. Here, we provide an in-depth analysis regarding the techno-economic benefits of replacing the mechanical gearbox with a hydraulic transmission in an offshore system. Our analysis shows that hydraulic transmissions are particularly beneficial for offshore applications: (i) relocating 35.3% of the nacelle mass to the base, thus moving the center of gravity toward the ground level, (ii) diminishing operation and maintenance costs, and (iii) replacing now-redundant power electronics. These three benefits contribute to saving between 3.92 and 18.8% on the Levelized Cost of Electricity for average cost offshore wind turbines. Highlights: The failure-prone gearbox is replaced by a hydraulic pump and a ground-level motor. The transfer of components to ground level leads to a 35% reduction of nacelle mass. Ground-level components allow for easier access, lowering maintenance costs. The transmission reduces the LCOE of an offshore wind turbine by 4–19%.